Develompment Of Al Mustajib Madarijul Ulum Islamic Boarding School In Kubil Environment, Cipocok Jaya Village Cipocok Jaya District In 2010 – 2022.: Perkembangan Pondok Pesantren Al Mustajib Madarijul Ulum Di Lingkungan Kubil Kelurahan Cipocok Jaya Kecamatan Cipocok Jaya Tahun 2010 - 2022 - Siti Fitriyah; Ana Nurhasanah; Rikza Fauzan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The aims of this study is to: 1) The early history of the founding of the Al Mustajib Madarijul Ulum Islamic boarding school, 2) development of the Salafi education system at the Al Mustajib Madarijul Ulum Islamic boarding school in 2010-2022 This research uses historical methods, including: heuristics, source criticism, interpretation and historiography. The results of this research include: 1) Al Mustajib Madarijul Ulum Islamic boarding school is led by a cleric named K.H Shobirin. The initial history of this Islamic boarding school was built simply in 1995, the name of the Islamic boarding school was taken from the names of the children of K.H. Shobirin, namely Al Mustajib and Madarijul Ulum, Al Mustajib means Prayer that is answered and Madarijul Ulum is taken from one of the names of the Islamic boarding school of K.H. Shobirin where he used to study. Al-Mustajib Madarijul Ulum Islamic Boarding School is located on Jalan Bhayangkara Lingkungan Kubil, RT / RW 001/012 Kelurahan Cipocok Jaya, Kecamatan Cipocok Jaya, Serang City, Banten Province. This Islamic boarding school was built on an area of ​​600 m2 around the residential area. 2) The development of the Al-Mustajib Madarijul Ulum Islamic boarding school can be seen from the development of the education system, infrastructure, and students who are increasingly advanced. From the infrastructure from the year it was founded until now, the Al-Mustajib Madarijul Ulum Islamic boarding school continues to increase its facilities. Then in the development of students from year to year, students who register at the Al-Mustajib Madarijul Ulum Islamic boarding school are increasing. And in the development of the Salafi education system, it is increasingly advanced and creative, starting from the rules, materials, activities, and teaching methods